Rubisco mutants of Chlamydomonas reinhardtii enhance photosynthetic hydrogen production - T. S. Pinto (2013)
Molecular hydrogen (H2) is an ideal fuel characterized by high enthalpy change and lack of greenhouse effects. This biofuel can be released by microalgae via reduction of protons to molecular hydrogencatalyzed by hydrogenases. The main competitor for the reducing power required by the hydrogenases is the Calvin cycle, and rubisco plays a key role therein. Engineered Chlamydomonas with reduced rubisco levels, activity and stability was used as the basis of this research effort aimed at increasing hydrogen production. Biochemical monitoring in such metabolically engineered mutant cells proceeded in Tris/acetate/phosphate culture medium with S-depletion or repletion, both under hypoxia. Photosynthetic activity, maximum photochemical efficiency, chlorophyll and protein levels were all measured. In addition, expression of rubisco, hydrogenase, D1 and Lhcb were investigated, and H 2 was quantified. At the beginning of the experiments, rubisco increased followed by intense degradation. Lhcb proteins exhibited monomeric isoforms during the first 24 to 48 h, and D1 displayed sensitivity under S-depletion. Rubisco mutants exhibited a significant decrease in O2 evolution compared with the control. Although the S-depleted medium was much more suitable than its complete counterpart for H2 production, hydrogen release was observed also in sealed S-repleted cultures of rubisco mutated cells under low-moderate light conditions. In particular, the rubisco mutant Y67A accounted for 10-15-fold higher hydrogen production than the wild type under the same conditions and also displayed divergent metabolic parameters. These results indicate that rubisco is a promising target for improving hydrogen production rates in engineered microalgae.